1984
DOI: 10.1007/bf00252269
|View full text |Cite
|
Sign up to set email alerts
|

Rat bladder in the early stages of streptozotocin-induced diabetes: adrenergic and cholinergic innervation

Abstract: Summary. The adrenergic and cholinergic innervation of the bladder was studied in streptozotocin-diabetic rats. The presence of hypertrophy and distension in the 'diabetic' bladders necessitates care in assessing changes occurring in the nerves, factors which are also relevant to clinical histochemical studies. Biochemical assays of cholinergic enzymes revealed decreased activities per g wet weight tissue. However, the total activities of choline acetyltransferase and acetylcholinesterase per whole bladder wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
46
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 33 publications
7
46
0
Order By: Relevance
“…In agreement with a previous study [9], the increase of VIP concentration in the expanded bladder of the diabetic Chinese hamster appears to be meaningful since it can be demonstrated on a pmol/organ basis. This contention is reinforced by the finding of increased acetylcholinesterase activity in the expanded bladder of streptozotocin-diabetic rats [9]. Furthermore, the elevation of VIP in the bladder of the diabetic Chinese hamster may be more meaningful since it has been shown that in-A.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In agreement with a previous study [9], the increase of VIP concentration in the expanded bladder of the diabetic Chinese hamster appears to be meaningful since it can be demonstrated on a pmol/organ basis. This contention is reinforced by the finding of increased acetylcholinesterase activity in the expanded bladder of streptozotocin-diabetic rats [9]. Furthermore, the elevation of VIP in the bladder of the diabetic Chinese hamster may be more meaningful since it has been shown that in-A.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is logical to hypothesize that an elevation in VIP may be one of the early complications related to bladder dysfunction in the diabetic Chinese hamster. Support for this hypothesis is derived from a previous investigation in which an increase in cholinergic nerve activity was observed in the distended bladders of short-term streptozotocin-diabetic rats [9]. It was also suggested that elevated cholinergic nerve activity in streptozotocin-diabetic rats is probably a compensatory response to allow the hypertrophied detrusor muscle to respond to increased volume and frequency of urine [10].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The motor activity of the smooth muscle, especially that of the bladder dome, is mainly regulated by the parasympathetic nervous system (8,9). Histochemical and functional studies have shown a DM-induced alteration in cholinergic innervation as well as an altered sensitivity to cholinergic agonists (10)(11)(12)(13). Recent in vitro studies showed that the contractile response to muscarinic agonists was increased about 50% in the bladder dome of rats with streptozotocin (STZ) induced DM (14,15), and this was accompanied by sig nificant increases in the densities of muscarinic receptors in the bladder dome of rats (14,16,17).…”
mentioning
confidence: 99%